IMPROVING THE QUALITY OF TEACHING RUSSIAN AS A FOREIGN LANGUAGE AT UNIVERSITIES (International journal of artificial intelligence, 2025)
This article analyzes strategies for improving the quality of teaching Russian as a Foreign Language (RFL) at the university level. It identifies the limitations of traditional grammar-translation methods and advocates for a holistic, systemic shift. This includes integrating communicative language teaching (CLT), digital technologies, and deep socio-cultural immersion. The discussion emphasizes that quality enhancement depends on institutional support for modern teacher training, flexible curricula tailored to Language for Specific Purposes (LSP), and the implementation of authentic assessment methods that measure true communicative and intercultural competence.